2022
DOI: 10.1186/s12936-022-04421-1
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic malaria infection, associated factors and accuracy of diagnostic tests in a historically high transmission setting in Northern Uganda

Abstract: Background Asymptomatic malaria infections are important parasite reservoirs and could sustain transmission in the population, but they are often unreported. A community-based survey was conducted to investigate the prevalence and factors associated with asymptomatic malaria infections in a historically high transmission setting in northern Uganda. Methods Using a cross-sectional design, 288 children aged 2–15 years were enrolled and tested for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
3
9
1
Order By: Relevance
“…On the other hand, compared to the current study, a higher prevalence of asymptomatic malaria infection was reported in the country [ 20 , 21 , 23 , 24 , 42 , 43 ] and elsewhere [ 44 , 45 ]. These variations could be attributed to several factors, including the group of the study population, geographical areas the study covered, sampling techniques, and the season of the study period as well.…”
Section: Discussioncontrasting
confidence: 90%
“…On the other hand, compared to the current study, a higher prevalence of asymptomatic malaria infection was reported in the country [ 20 , 21 , 23 , 24 , 42 , 43 ] and elsewhere [ 44 , 45 ]. These variations could be attributed to several factors, including the group of the study population, geographical areas the study covered, sampling techniques, and the season of the study period as well.…”
Section: Discussioncontrasting
confidence: 90%
“…Furthermore, the types of malaria parasites prevalent in Sudan could play a role in the lack of association between fever and malaria positivity. Some species of malaria are known to cause asymptomatic infections or present with atypical symptoms, including absence of fever [36,37]. Overall, the lack of a signi cant association between fever and malaria positivity in the studied population highlights the complexity of diagnosing febrile illnesses in malaria-endemic regions and underlines the importance of exploring alternate diagnostic approaches and screening for a wide range of infectious and noninfectious causes of fever.…”
Section: Discussionmentioning
confidence: 99%
“…Although malaria poses the greatest risk for morbidity and mortality in children under 5, recent studies highlight a significant burden of asymptomatic malaria in school aged children and their major role in transmission. Rates of rapid diagnostic test (RDT) positive asymptomatic malaria in school-aged children (age 5–15) ranged from 18% to 47% in recent studies, depending on study site and design [28–30,31 ▪ ]. The PCR positivity rate was 22% to 86% [29,30,31 ▪ ,32–34].…”
Section: Malaria In School Aged Childrenmentioning
confidence: 99%